2021
DOI: 10.1093/jme/tjab189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climate on the Variation in Abundance of Three Tick Species in Illinois

Abstract: The range of ticks in North America has been steadily increasing likely, in part, due to climate change. Along with it, there has been a rise in cases of tick-borne disease. Among those medically important tick species of particular concern are Ixodes scapularis Say (Acari: Ixodidae), Dermacentor variabilis Say (Acari: Ixodidae), and Amblyomma americanum Linneaus (Acari: Ixodidae). The aim of this study was to determine if climate factors explain existing differences in abundance of the three aforementioned ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…Field studies would complement insights from laboratory experiments that use this protocol. For example, field observational studies in New York, New Jersey, Rhode Island, and Illinois showed that RH and precipitation affect questing activity and abundance patterns of A. americanum, D. variabilis, and I. scapularis [35,[45][46][47][48]. Additional experiments showed that microclimatic conditions affect survival of Ixodes ticks, although questing behavior depends largely on geographic origin of populations, suggesting local ecological adaptation [43,49].…”
Section: Limitations and Broader Applicationsmentioning
confidence: 99%
“…Field studies would complement insights from laboratory experiments that use this protocol. For example, field observational studies in New York, New Jersey, Rhode Island, and Illinois showed that RH and precipitation affect questing activity and abundance patterns of A. americanum, D. variabilis, and I. scapularis [35,[45][46][47][48]. Additional experiments showed that microclimatic conditions affect survival of Ixodes ticks, although questing behavior depends largely on geographic origin of populations, suggesting local ecological adaptation [43,49].…”
Section: Limitations and Broader Applicationsmentioning
confidence: 99%
“…In the study area, diverse tick species were observed amongst different livestock and associated animals. The diversity of tick species might be due to the climatic conditions, which are favorable for the development of many tick species (29). The ticks identified in this study are known to be facilitators of several tick-borne infections (30).…”
Section: Discussionmentioning
confidence: 93%
“…The ticks identified in this study are known to be facilitators of several tick-borne infections (30). Several tick species that belong to the genera Rhipicephalus, Hyalomma, Haemaphysalis, and Ixodes have been reported previously (19,20,(29)(30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%
“…These include foliage composition, temperature, humidity, day length and seasonality (Ludwig et al 2016). Cold winters are known to limit the survivorship of overwintering ticks (Semtner and Hair 1976, Kaizer et al 2015, Linske et al 2019, Bacon et al 2021), so it might not be purely coincidence that both in New England and the northern central U.S., populations of A. americanum are emerging initially along coastal habitats, which have more moderate winters relative to areas further inland. It is unknown how A. americanum may have been introduced into northwest Indiana, whether via terrestrial hosts or migrating birds, but there are records of low numbers of A. americanum collected via a combination of passive and active surveillance from the three northwest counties bordering Lake Michigan since the late 1990s and evidence of established populations since 2005 (L. Green, Indiana Department of Health, pers.…”
Section: Discussionmentioning
confidence: 99%